Pengujian Aplikasi Scantion Menggunakan Metode Blackbox dengan Teknik Equivalence Partitioning - Efda, Mohamad Rehza; Nuryasin, Ilyas (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Software testing is needed to ensure that the application or software that is being made can run according to the expected functionality. Testing an application aims to determine whether the application operates as desired or there are still errors that need to be corrected. This study aims to determine whether the Scantion application has run according to its function, and evaluate whether the form in the application can accept various situations or inputs that may occur during the application is operated, therefore a functionality test is carried out using the Blackbox testing method with the Equivalence Partitioning technique. The Blackbox testing method is carried out to check the system interface function whether it is appropriate or not, by only focusing on the output results based on the input given, without paying attention to the program code used. As well as the Equivalence Partitioning technique which is a technique of dividing inputs into data partitions with valid and invalid values, this is effective for minimizing the number of test cases needed. The test results show a Scantion success rate of 100%, where each test case that has been made is successfully executed as expected and the application manages user input properly according to its function. Thus, this application has the potential to be a solution to support skin cancer detection efforts.